Can Tocqueville karaoke? - Clark, Terry Nichols, 1940- (Bingley, U.K. : Emerald, 2014)
This volume questions the importance of arts and culture and their possible impact on politics and the economy. Chapters outline a new framework for analysis of democratic participation and economic growth and explore how these new patterns work around the world. The ideas of Alexis de Tocqueville and Joseph Schumpeter and Jane Jacobs are analysed.
Introduction / Terry Nichols Clark -- Karaoke together vs. bowling alone : scenes illuminate how Western rules can be transformed to drive development and democracy / Terry Nichols Clark ... [et al.] -- Voluntary associations, social inequality, and participatory democracy in the United States and Korea / Seokho Kim -- Citizen participation in Seoul, Tokyo, and Chicago / Wonho Jang, Terry Nichols Clark, Miree Byun -- From bowling alone to Karate together (USA to Asia) : preliminary claims & findings / Joseph E. Yi -- Civic and arts activities can energize politics, France and Europe / Daniel J. DellaPosta ... [et al.] -- Cultural strategies, creativity, and local development in Spain / María Jesús Rodríguez-García, Cristina Mateos Mora, Clemente J. Navarro Yáñez -- (Re)defining bohemia in Seoul, Tokyo, and Chicago / Wonho Jang, Terry Nichols Clark, Miree Byun -- Was Tocqueville wrong? Buzz as charisma, creativity, and glamour; new sources of political legitimacy supplementing voting, and civic participation / Terry Nichols Clark, Filipe Carreira da Silva -- Buzz : a theory, illustrated in Toronto and Chicago / Daniel Silver, Terry Nichols Clark -- Culture is on the rise : why? Theories of cultural participation and empirical evidence / Terry Nichols Clark, Peter Achterberg -- How context transforms citizen participation : propositions / Filipe Carreira da Silva, Terry Nichols Clark -- The contextual effect of local scenes on cultural practices : the case of Spain / Clemente J. Navarro Yáñez, María Jesús Rodríguez-García -- Global contexts of politics and arts participation / Terry Nichols Clark, Filipe Carreira da Silva, Susana L. Farinha Cabaço.
Includes index.
Print version record
Keywords: Tocqueville, Alexis de, -- 1805-1859.; Schumpeter, Joseph A., -- 1883-1950.; Jacobs, Jane, -- 1916-2006.; Political Science -- Public Policy -- Cultural Policy; Cultural studies; Political science & theory; Political science